Determination of the triple oxygen and carbon isotopic composition of CO2 from atomic ion fragments formed in the ion source of the 253 Ultra high‐resolution isotope ratio mass spectrometer. (5th August 2019) - Adnew, Getachew A.; Hofmann, Magdalena E.G.; Paul, Dipayan; Laskar, Amzad; Surma, Jakub; Albrecht, Nina; Pack, Andreas; Schwieters, Johannes; Koren, Gerbrand; Peters, Wouter; Röckmann, Thomas
Abstract : Rationale: Determination of δ 17 O values directly from CO2 with traditional gas source isotope ratio mass spectrometry is not possible due to isobaric interference of 13 C 16 O 16 O on 12 C 17 O 16 O. The methods developed so far use either chemical conversion or isotope equilibration to determine the δ 17 O value of CO2 . In addition, δ 13 C measurements require correction for the interference from 12 C 17 O 16 O on 13 C 16 O 16 O since it is not possible to resolve the two isotopologues. Methods: We present a technique to determine the δ 17 O, δ 18 O and δ 13 C values of CO2 from the fragment ions that are formed upon electron ionization in the ion source of the Thermo Scientific 253 Ultra high‐resolution isotope ratio mass spectrometer (hereafter 253 Ultra). The new technique is compared with the CO2 ‐O2 exchange method and the 17 O‐correction algorithm for δ 17 O and δ 13 C values, respectively. Results: The scale contractions for δ 13 C and δ 18 O values are slightly larger for fragment ion measurements than for molecular ion measurements. The δ 17 O and Δ 17 O values of CO2 can be measured on the 17 O + fragment with an internal error that is a factor 1–2 above the counting statistics limit. The ultimate precision depends on the signal intensity and on the total time that the 17 O + beam is monitored; a precision of 14 ppm (parts per million) (standard error of the mean) was achieved in 20 hours at the University of Göttingen. The Δ 17 O measurements with the O‐fragment method agree with the CO2 ‐O2 exchange method over a range of Δ 17 O values of −0.3 to +0.7‰. Conclusions: Isotope measurements on atom fragment ions of CO2 can be used as an alternative method to determine the carbon and oxygen isotopic composition of CO2 without chemical processing or corrections for mass interferences.